Choice of currency to tie the proposed West African currency, the ECO, to: Some empirical insight - Abdul Salam Sikiru Abidemi; Muhammad Aminu Ado (West African Journal of Monetary and Economic Integration, 2021)
This study examined whether the proposed West African currency, the ECO, should be tied to the US dollar, Euro, Naira, or CFA? The study partitions the four currencies into two groups: (i) already internationalized currencies (US dollar and Euro); and (ii) emerging currencies for internationalization within ECOWAS (Naira and CFA). Consequently, empirical modelling using panel OLS was conducted on the first group; thereafter, the estimated parameters are used for forecasting under the assumption of a smooth economic condition. Empirical results show that the size of an economy, trade level, and exchange rate are significant determinants in adopting a peg or anchor currency. In addition, the result of the simulation analysis shows that the US dollar has a higher internationalization potential than the Euro. The study also found that the Nigerian Naira has a higher internationalization potential compared to the CFA franc. Thus, the study recommends adopting the US dollar as the currency to tie the ECO currency to and, within the ECOWAS zone, advocates for the use of the Nigerian Naira.
Keywords: 330; International reserves; Exchange Rate Mechanism; panel OLS